Formation of metal-radical species upon reduction of late transition metal complexes with heteroleptic ligands: an experimental and theoretical study. (22nd July 2020) - Malček, Michal; Kožíšková, Júlia; Herich, Peter; Rapta, Peter; Stepanenko, Iryna; Arion, Vladimir B.
Abstract : Three novel transition metal complexes with selenadiazoloquinolones as potential broad spectrum antibiotics in clinical praxis. Abstract : A series of three new metal complexes with selenadiazoloquinolones, known as broad spectrum antibiotics in clinical praxis, namely [Co(E4 h )2 (phen)]·8H2 O (1 ), [Ni(E4 h )2 (phen)]·8H2 O (2 ) and [Cu(E4 h )(phen)Cl]·5H2 O (3 ), have been synthesized and fully characterized by analytical methods, ESI mass spectrometry, single crystal X-ray crystallography, cyclic voltammetry (CV), and in situ EPR/UV-vis-NIR spectroelectrochemistry supported by theoretical calculations. For 1 and 2 two-electron transfer leads to the formation of a paramagnetic dianion with the spin density localized on the two weakly interacting selenadiazole moieties. For 3 the first reduction step represents a reduction process on the central atom, while the second reversible reduction step occurs on the selenadiazole moiety. The formation of a radical anion of selenadiazoloquinolone upon cathodic reduction was confirmed both experimentally and by DFT calculations. The optimized geometries were compared with the geometric parameters resulting from single crystal X-ray diffraction data, and the bonding in 1–3 was inspected via analysis of bond critical points (BCP) under the formalism of Bader's quantum theory of atoms in molecules (QTAIM).